Examining Moves and Steps in Discussion Chapters of TEFL Master’s Theses by Indonesian Postgraduates: A Genre Analysis - Dalimunte, Ahmad Amin; Ritonga, Gustina Permatasari; Fathani, Jihan Aldie (Universitas Muhammadiyah Kalimantan Timur, 2024)
The discussion chapter holds a paramount position in a thesis, being regarded as the most crucial and challenging part to compose, particularly for university students. The present genre investigation highlighted the focus on language use and communicative practices. This research seeks to investigate the rhetorical organization, moves, and steps, employed by Indonesian postgraduates while writing the discussion chapter of their theses within the field of Teaching English as a Foreign Language (TEFL). We examined five theses from postgraduate students whose data were obtained from the university repository. Data were analyzed with the framework proposed by Chen and Kuo (2012). The overall word count is 9204 words. From the analysis conducted, it was found that Move 2 Step 1: Reporting major findings (41.4%), Move 4 Step 2: comparing the results with literature (21.9%), and Move 4 Step 3: accounting for results (20.7%) were highly used in the data. However, two steps were least used in the data; namely, Move 3 Step 1: making conclusions of results and Move 6 Step 2: indicating the significance of the study. Our findings provide insights into how postgraduates structure their arguments, present findings, and interact with existing literature.